Clasificación bidimensional de emociones percibidas al escuchar música, usando Machine Learning (2020)
This document describes the work carried out in the search for the most appropriate model to classify emotions in a two-dimensional plane, as a result of the emotional perception of a person when listening to music. The context of the problem, the theory used as a basis, the work methodology, the comparative results, conclusions, future works and the implication of this work in the study of Music Emotion Recognition are exposed in this document.